Improvement in walking impairment following surgical and endovascular revascularization: Insights from VOYAGER PAD. (August 2022) - Hogan, Shea E; Nehler, Mark R; Anand, Sonia; Patel, Manesh R; Debus, Sebastian; Jackson, Matthew T; Buchanan, Cullen; King, R Wilson; Hess, Connie; Muehlhofer, Eva; Haskell, Lloyd P; Bauersachs, Rupert M; et al.
Background: Peripheral artery disease (PAD) affects 200 million people worldwide and is associated with impaired quality of life, increased morbidity, and mortality. Supervised exercise therapy (SET) and lower-extremity revascularization (LER) are both proven strategies to improve patient symptoms. Short and long-term functional outcomes after LER for symptomatic PAD in a large, international cohort have not previously been described. Methods: The VOYAGER PAD trial (ClinicalTrials.gov identifier: NCT02504216) enrolled subjects after LER for symptomatic PAD (Rutherford category 2–6). Participants completed the Walking Impairment Questionnaire (WIQ) at baseline, 1, 3 and 6 months, and every 6 months thereafter. The primary outcome analysis was degree of difficulty walking two blocks at each of the aforementioned time points. Difficulty walking three blocks and climbing one flight of stairs at these time points was also analyzed. Data about supervised and home exercise therapy before or after revascularization were not collected in the VOYAGER PAD trial. Results: Of the 5614 VOYAGER PAD participants completing the WIQ at baseline, three-quarters presented with claudication and one-quarter with critical limb ischemia. Of these, the majority (62% with claudication and 74% with CLI) reported inability or much difficulty walking two blocks prior to LER. Walking improved after LER regardless of revascularization strategy, but one-fifth with claudication and one-third with CLI reported continued inability or much difficulty walking two blocks 1 month after LER. Participants who reported improved walking ability 1 month after LER experienced a durable functional result out to 3 years. Although the proportion of participants reporting significant baseline difficulty climbing one flight of stairs or walking three blocks differed, the trend in immediate and sustained improvement after LER was similar to that observed for walking two blocks. Conclusion: In this large, international cohort undergoing LER for symptomatic PAD, nearly two-thirds reported inability or much difficulty walking two blocks at baseline. Although many participants reported improved walking ability after LER, a substantial proportion remained severely disabled. These observations may help motivate providers, patients, and medical systems to improve awareness and engagement in SET referral after LER.